Dominant Factors Affecting the Development of Religious Values and Morals of Early Childhood in Childhood Early Education - Zulkifli N (Journal of Educational Sciences, 2019)
The the development of religious and moral values for early childhood is an important foundation process to form the resilient characters for the nation's children in 25-45 years ahead. The objective of this research is to describe the achievement level of early childhood development, analysis of the dominant factors that shape the development aspects of religious and moral values of children aged 4-6 years in PAUD District Kuok, Kampar. The research methodology used in this study was a survey in the form of quantitative descriptive. The research findings show that the achievement of early childhood development rates for ages 4-6 years, from 6 indicators, it turns out that most of the children in the category developed based on expectations (BSH = 65.50%) and developed very well (BSB = 11, 36%). Meanwhile, internal and external factors are both dominant and conducive to the development of the religious and moral values toward early childhood in the Kuok Sub-District Kindergarten, Kampar. The implication needs more focused research on the values of religious and moral value development of children in the context of local wisdom in line with the motto of Kampar "Serambi Mekkah/The Foyer of Mecca", Nagari Bersendikan Sarak, Sarak Bersendikan Kitabullah dan Sunnatulloh (a city based on Sharia and Sharia-based on Qur'an and Sunnah of the prophet).